Identification of novel vibration- and deflection-sensitive neuronal subgroups in Johnston's organ of the fruit fly - Matsuo, Eriko; Yamada, Daichi; Ishikawa, Yuki; Asai, Tomonori; Ishimoto, Hiroshi; Kamikouchi, Azusa (Frontiers in Physiology, 2014)
The fruit fly Drosophila melanogaster responds behaviorally to sound, gravity, and wind. Johnston's organ (JO) at the antennal base serves as a sensory organ in the fruit fly to detect these mechanosensory stimuli. Among the five anatomically defined subgroups of sensory neurons in JO, subgroups A and B detect sound vibrations and subgroups C and E respond to static deflections, such as gravity and wind. The functions of subgroup-D JO neurons, however, remain unknown. In this study, we used molecular-genetic methods to explore the physiologic properties of subgroup-D JO neurons. Both vibrations and static deflection of the antennal receiver activated subgroup-D JO neurons. This finding clearly revealed that zone D in the antennal mechanosensory and motor center (AMMC), the projection target of subgroup-D JO neurons, is a primary center for antennal vibrations and deflection in the fly brain. We anatomically identified two types of interneurons downstream of subgroup-D JO neurons, AMMC local neurons (AMMC LNs), and AMMC D1 neurons. AMMC LNs are local neurons whose projections are confined within the AMMC, connecting zones B and D. On the other hand, AMMC D1 neurons have both local dendritic arborizations within the AMMC and descending projections to the thoracic ganglia, suggesting that AMMC D1 neurons are likely to relay information of the antennal movement detected by subgroup-D JO neurons from the AMMC directly to the thorax. Together, these findings provide a neural basis for how JO and its brain targets encode information of complex movements of the fruit fly antenna.